Islamic Counseling Integration for Migrant Parents’ Students: A Socio-Cultural Approach in Islamic Educational Context - Muhammad Maulidi; Misnawi Misnawi (Institut Attanwir Bojonegoro, 2025)
The phenomenon of Indonesian migrant labor has created complex socio-cultural challenges requiring innovative approaches within Islamic educational contexts. This study examines how Islamic counseling principles can be integrated with modern psychological approaches to address the psychosocial needs of students with migrant parents at Madrasah Aliyah Ummul Quro. Using a qualitative descriptive approach, this research explores the integration of Islamic values (tazkiyah, sabar, and tawakkal) with contemporary counseling techniques in addressing social and emotional well-being challenges. The study involved students with migrant parents, Islamic guidance counselors, and school administrators. Data collection employed non-participatory observation, semi-structured interviews, and document analysis, analyzed through Miles & Huberman’s interactive model. Findings reveal that Islamic counseling integration provides culturally appropriate solutions by combining Quranic guidance, prophetic traditions, and modern psychological principles. The socio-cultural approach demonstrates effectiveness in addressing unique challenges within transnational family structures while maintaining Islamic identity and values. The integrated model shows significant potential for Islamic educational institutions in addressing contemporary social challenges while preserving religious authenticity. This study contributes to the development of Islamic counseling theory and provides practical frameworks for madrasah-based guidance services.